An insight on the association of glycation with hepatocellular carcinoma. (April 2018) - Jabir, Nasimudeen R.; Ahmad, Saheem; Tabrez, Shams
Abstract: Hepato-cellular carcinoma (HCC) is one of the frequent cause of cancer-related death worldwide and dominant form of primary liver cancer. However, the reason behind a steady increase in the incidence of this form of cancer remains elusive. Glycation has been reported to play a significant role in the induction of several chronic diseases including cancer. Several risk factors that could induce HCC have been reported in the literature. Deciphering the complex patho-physiology associated with HCC is expected to provide new targets for the early detection, prevention, progression and recurrence. Even-though, some of the causative aspects of HCC is known, the advanced glycation end products (AGEs) related mechanism still needs further research. In the current manuscript, we have tried to uncover the possible role of glycation in the induction of HCC. In the light of the available scientific literature, we advocate in-depth comprehensive studies which will shed light towards mechanistic association of glycation with HCC.